Decoding Vitex altissima L.: A review of its ethnobotanical heritage, phytochemical composition and therapeutic potential - Patil, Sachin; Devkar, Suraj; Deshmukh, Sagar (Ethnobotany Research and Applications, 2025)
Background: Vitex altissima L. known as the "Peacock Chaste Tree" belongs to the Verbenaceae (Lamiaceae) family. Traditionally it is used for furniture making, relieve rheumatic swellings and body pain. The plant has gained attention for its significant pharmaceutical potential in traditional Chinese medicine as its bark and roots are used to treat rheumatism and pain. The plant’s rich content of alkaloids, saponins, flavonoids and phenolic compounds contribute to its antioxidant, anti-inflammatory and antimicrobial properties. Methods: This review aims to gain a comprehensive understanding of Vitex altissima L. by conducting an extensive literature search using platforms such as PubMed, ScienceDirect, Google Scholar, Ayush, e-Charaka, SpringerLink and relevant books. Results: Vitex altissima L. is traditionally utilized by ethnic and tribal groups in South India to treat various ailments, including urinary disorders, stomatitis, ulcers and jaundice. The plant is rich in phytochemicals such as flavonol glycosides, flavonoids, steroidal saponins, alkaloids etc. includes compounds like agnuside, negundoside, corosolic acid, vitexin, altissinone, quercetin, tetradecanoic acid, viridiflorol etc. These compounds underpin the plant’s broad pharmacological activities, comprising antimicrobial, anthelmintic, antiviral, wound healing, anti-inflammatory, antioxidant, anticancer, hepatoprotective, nephroprotective, insecticidal and larvicidal effects. Conclusion: This review highlights Vitex altissima L. as a potent source of phytochemicals with substantial pharmacological value, contributing to our understanding of its biological activities and offering potential for advancements in medicinal and industrial fields in future. Keywords: Vitex altissima L., Review, Ethnobotany, Pharmacology.